Chicory (Cichorium intybus L.) and plantain (Plantago lanceolata L.) inclusion improves some growth, production, and carcass characteristics of guinea pigs (Cavia porcellus L.) in the Peruvian highlands - Pariona Rodas, Shirley B. (2026)
Background: Alternative forages, such as chicory and plantain, have been successfully applied in various animal species. As a result, these forages could serve as an alternative for raising guinea pigs in high Andean regions; however, few, if any, reports have been published on the effects of their inclusion on growth, production, and carcass yield. Aim: This study aimed to determine the effects of incorporating chicory and plantain into the diet of guinea pigs on growth, production, and carcass yield, elucidating the possibility of using these species for feeding guinea pigs. Methods: The study was conducted in Andahuaylas—Perú, in an experimental period of 6 weeks. Five guinea pigs were randomly assigned to each diet treatment (30% chicory–70% lucerne, 30% plantain–70% lucerne, 50% chicory–50% lucerne, 50% plantain–50% lucerne, and 100% lucerne as a control). Growth, production, and carcass yield were measured. Covariance analysis was performed using R software, and the means were compared using Dunnett's method (α=0.05). Results: Diets with chicory (30%–50%) improved the final live weight, weight gain, feed conversion ratio, and hot carcass weight, whereas diets with plantain (30%) improved the final live weight, dry matter intake, feed conversion ratio, and carcass weight compared with diets with 100% lucerne. Conclusion: Chicory and plantain can optimize the growth, production, and hot carcass weight of guinea pigs in high Andean areas, surpassing traditional lucerne diets.